Using an Implementation Trial of an ePortfolio System to Promote Student Learning through Self-Reflection: Leveraging the Success - Chris Campbell; Tran Le Nghi Tran (MDPI AG, 2021)
This paper reports on a pilot study that was conducted during a technical trial of a new ePortfolio system at a large Australian university. Students from a large (n = 325) first-year educational technology course were given the opportunity to use the new ePortfolio system weekly as part of their reflective practice at the end of the hands-on tutorial classes and also through a blogging assignment that required six posts throughout the semester. Although the students reflecting on their work and ePortfolios themselves are not new concepts, this paper reports how assessment practices can be improved using ePortfolios and how students can improve their reflective practice through simple and regular use throughout the 12-week semester that the study was conducted. From the class, 208 students responded to the survey with the results being positive. The students were able to use the system easily and did not report many problems with crashing or freezing. The lessons learnt form an important part of this study for future iterations with these reported in the paper.